Increasing Students' Economic Independence Through Economic Security-Based Entrepreneurship at Ibnu Sina Banten High School - Farhana, Husna; Simorangkir, Rona Tumiur Mauli Carolin; Sari, Pratiwi Nila; Ningrum, Desy Tya Maya; Syifa, Mahda; Dalilah, Evi (GANDRUNG: Jurnal Pengabdian Kepada Masyarakat, 2025)
Margaluyu Village, Banten faces several social and economic problems, including students dropping out of school due to the loss of their parents' livelihoods, motivation to go to school, and students having difficulty finding work after graduating. To overcome these challenges, entrepreneurship training based on economic security is needed, with the aim of creating economic independence for students and the local community. This village has great agricultural and plantation potential, but marketing of agricultural products is limited due to dependence on middlemen. Through a business incubation program, students are expected to develop skills in optimally utilizing agricultural products, managing businesses, and selling products using social media such as Instagram and TikTok. SMA Ibnu Sina was chosen as a model school for this program, with a focus on entrepreneurship education which is expected to equip students with practical skills and build an entrepreneurial spirit. This program also involves students as part of the MBKM program, which aims to strengthen academic relationships with the community and increase sensitivity to local problems. The main objective of this service is to help SMA Ibnu Sina students in Margaluyu Village develop the local economy and create new business opportunities, as well as support increasing students' economic independence through sustainable entrepreneurship practices.